Integrating Exposure and Effect Distributions with the Ecotoxicity Risk Calculator: Case Studies with Crop Protection Products. (30th October 2020) - Dreier, David A; Rodney, Sara I; Moore, Dwayne RJ; Grant, Shanique L; Chen, Wenlin; Valenti, Theodore W; Brain, Richard A
ABSTRACT: Risk curves describe the relationship between cumulative probability and magnitude of effect and thus express far more information than risk quotients. However, their adoption has remained limited in ecological risk assessment. Therefore, we developed the Ecotoxicity Risk Calculator (ERC) to simplify the derivation of risk curves, which can be used to inform risk management decisions. Case studies are presented with crop protection products, highlighting the utility of the ERC at incorporating various data sources, including surface water modeling estimates, monitoring observations, and species sensitivity distributions. Integr Environ Assess Manag 2021;17:321–330. © 2020 Syngenta Crop Protection, LLC. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: Risk curves describe the relationship between distributions of exposure and effect. The Ecotoxicity Risk Calculator can be used to generate risk curves from various data sources. Case studies are presented with risk curves for crop protection products.